A study on making complete feed blocks for cattle with different combination of fodder grasses and agricultural wastes - Santhiralingam, S.; Sinniah, J. (International Journal of Scientific and Research Publications, 2018)
Present study was carried out to develop a cost effective complete feed block with long shelf life using locally available fodder grasses and agricultural wastes. Three different complete feed blocks (T1, T2 and T3) were formulated to meet the daily requirement of 250kg heifers. Compacted blocks were formed in T1 and T2, while, T3 formed loose mass. The lowest (P< 0.05) free fatty acid content was observed in T2 while T3 had the highest. The highest (P< 0.05) dry matter, ash, ether extract, crude fiber and acid detergent fiber percentage were recorded in T1. Higher (P< 0.05) neutral detergent fiber, calcium and phosphorus contents were observed in T2 compared to T1 and T3. The highest (P< 0.05) crude protein and total digestible nutrient content were recorded in T3. The costs of production of T1, T2 and T3 to fulfil daily requirement of a heifer (250 kg) were Rs 130.55, Rs 149.75, and Rs 160.60, respectively. Based on the findings of this study, the feed block T3 found to be the best considering total digestible nutrient and crude protein contents but it failed to form the compact block, hence in the present form it is not suitable to make the complete feed block. Considering the shelf life and cost of production, the feed block T1 found to be the best. However, a feeding trial is required to evaluate the growth rate and feed conversion efficiency of heifers to select the best complete feed block.
Keywords: Agricultural wastes; Complete feed block; Fodder grasses; Nutritive values